Novel 8%-TiO2-nanoparticle-reinforced dense polycrystalline bovine hydroxyapatite bioceramic - de Azevedo-Silva, Lucas José; Ferrairo, Brunna Mota; Pires, Luara Aline; Padovini, David Santos Souza [UNESP]; Dias, Leonardo Francisco Gonçalves [UNESP]; Erbereli, Rogério; Fortulan, Carlos Alberto; Lisboa-Filho, Paulo Noronha [UNESP]; Rubo, José Henrique; Borges, Ana Flávia Sanches (Wiley, 2022)
This study aimed to produce and characterize the microstructure and mechanical properties of dense polycrystalline bovine hydroxyapatite (DPBHA) bioceramics with 5% and 8% of TiO2 nanoparticles after final synthetization for future use in dental implants. Structural characterization was obtained from analyzes by Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscope, energy dispersive spectroscopy, and relative density and apparent porosity. The mechanical characterization was performed by measuring the fracture toughness after three-point flexural strength (FS) test. The microstructural characterization results showed no secondary phase formation and nonhomogeneous nanoparticle dispersion in HA matrix. DPBHA/Np8% (2.9 ± 0.09 g/cm3) exhibited significantly greater density than DPBHA (2.7 ± 0.03 g/cm3) (p = 0.011) and DPBHA/Np5% (2.7 ± 0.05 g/cm3) (p = 0.041). DPBHA (0.9%) had the smallest porosity followed by DPBHA/Np8% (3.4%). DPBHA/Np5% (4.5%) exhibited the greatest proportion of pores. Pure HA (51.7 ± 10.3 MPa) and DPBHA/Np8% (47.4 ± 6.4 MPa) had significant greater FS (p < 0.001) than DPBHA/Np5% (28.8 ± 3.1 MPa). DPBHA (0.43 ± 0.01 MPa m1/2) and DPBHA/Np8% (0.40 ± 0.06 MPa m1/2) presented greater KIc than DPBHA/Np5% (0.23 ± 0.02 MPa m1/2) (p < 0.003; p < 0.007). In conclusion, 8% TiO2 nanoparticle addition to this synthesis would be a promising HA blend, as mechanical properties were similar, and the relative density/apparent porosity showed superior results than those of the DPBHA.
Keywords: bioceramics; hydroxyapatite; nanoparticles